Small Molecules Which Improve Pathogenesis of Myotonic Dystrophy Type 1 - López-Morató, Marta; Brook, John David; Wojciechowska, Marzena (Frontiers in Neurology, 2018)
Myotonic dystrophy type 1 (DM1) is the most common muscular dystrophy in adults for which there is currently no treatment. The pathogenesis of this autosomal dominant disorder is associated with the expansion of CTG repeats in the 3’-UTR of the DMPK gene. DMPK transcripts with expanded CUG repeats (CUGexpDMPK) are retained in the nucleus forming multiple discrete foci, and their presence triggers a cascade of toxic events. Thus far, most research emphasis has been on interactions of CUGexpDMPK with the muscleblind-like (MBNL) family of splicing factors. These proteins are sequestered by the expanded CUG repeats of DMPK RNA leading to their functional depletion. As a consequence, abnormalities in many pathways of RNA metabolism, including alternative splicing, are detected in DM1. To date, in vitro and in vivo efforts to develop therapeutic strategies for DM1 have mostly been focused on targeting CUGexpDMPK via reducing their expression and/or preventing interactions with MBNL1. Antisense oligonucleotides targeted to the CUG repeats in the DMPK transcripts are of particular interest due to their potential capacity to discriminate between mutant and normal transcripts. However, a growing number of reports describe alternative strategies using small-molecule chemicals acting independently of a direct interaction with CUGexpDMPK. In this review, we summarize current knowledge about these chemicals and we describe the beneficial effects they caused in different DM1 experimental models. We also present potential mechanisms of action of these compounds and pathways they affect which could be considered for future therapeutic interventions in DM1.